Factors Influencing the Formation of Antisocial Personality Disorder and Intervention Measures - Zhang, Wanlin (SHS web of conferences, 2023)
With the improvement of people’s material living standards, people’s attention to health has expanded from the original physical level to the psychological level. Since entering the 21st century, people have more and more problems on the psychological level. Normally, people with mental illnesses such as depression and anxiety only harm themselves, but for people with antisocial personality disorder, they affect not only themselves, but the whole society. In order to alleviate the social problems caused by antisocial personality disorder, it is necessary to understand the causes of the formation of antisocial personality disorder and formulate corresponding countermeasures according to these reasons. At present, there are many researches on ASPD, and the research content of this paper is to comprehensively elaborate the literature content on ASPD, and then get a general understanding of the formation and solution of ASPD. Based on the analysis of previous literatures on ASPD, and combined with the current social reality, this paper discusses the causes and countermeasures of ASPD. This study finds that the main causes of ASPD in adolescents are childhood trauma, physical problems, and the overall social environment. As for the solution, there are mainly empathy training and psychological nursing intervention. Based on this study, the final conclusion is that people should pay attention to the growth process of adolescents, create a more favorable growth environment for adolescents, and provide training and nursing treatment support for adolescents who have ASPD.